eLearning im „MOOseum Mathematik“: Erfahrungen mit einer flexiblen Internet- Lernumgebung für das Lehramtsstudium Mathematik (mathematica didactica, 2002)
In the paper I present my experiences in working with an open source learning environment in the internet, which was filled with content by my students during two terms. A report of the results and reactions of the students is given.